Drying kinetics of some varieties of pears produced in Portugal. - Guiné, Raquel (2013)
In this study, the solar drying behaviour of two varieties of pears produced in Portugal was investigated. To accomplish this, pears of the varieties Rocha and Rosa were dried whole, after peeling, by direct sun exposure, and measurements of their moisture content were conducted along the process. The experimental data was later used to test different empirical kinetic models, namely a cubic and an exponential decay function to fit the batch drying data and a first order kinetics and the Page equation to fit the drying rate data. From the present work was possible to conclude that the two varieties of pears studied show a similar drying behaviour and that the drying curves are better described by the exponential rather than the cubic function. As to the drying rate curves, the fits obtained with the Page equation are the ones which better represent the process over the entire time range.